A relação trabalho-educação e o projeto político-pedagógico do MST: uma prática em construção em escolas de assentamentos em Minas Gerais - Adilene Goncalves Quaresma (2011)
The present thesis of Doctorate had the aim of analyzing the relation between work-education. Starting with the research question that notes an absence seizure of the pedagogical aspects of work-education relation on studies about the work-education themes, we pursuit to identify and comprehend the philosophical and pedagogical aspects of this relation in an emancipatory perspective of education. The theoretical research, therefore, understood the discussion about work and pedagogy in the relation work-education. As a starting point, the research considers work category as first order intercession on human sociability process, trying to understand the ontological dimension of work. The theoretical reference used had Marx (2002, 1987 and 1980), Lukács (1979), Dewey (1952), Freire (2008,2006,2005,1983 e 1978), Organista (2006), Pochmann (2009) e Dal Rosso (2008), Menezes Neto (1999, 2001 and 2003), Frigotto (2003 e 2009), Kuenzer (1988, 1992 and 2007), Soares (2000), Machado (2005), Savianni (2005, 2006 e 2007), Souza Junior (2010) e Pistrak (2010), among others, for the comprehension of the relation between work and education. The empirical research was performed in three schools of settlements of the MST in Minas Gerais and understood in the data collection observations of classroom activities, questionnaires and interviews with students, educators and leaders of the Movement. In the course of theoretical research and methodological treatment of data, the references are based on the dialectical materialism, undertaking a qualitative study, combined with quantitative analyses